The Role of Single Talker Acoustic Variation in Early Word Learning - Galle, Marcus E. (Lang Learn Dev, 2014)
Recent work has demonstrated that the addition of multiple talkers during habituation improves 14-month-olds’ performance in the switch task (Rost & McMurray, 2009). While the authors suggest that this boost in performance is due to the increase in acoustic variability (Rost & McMurray, 2010), it is also possible that there is something crucial about the presence of multiple talkers that is driving this performance. To determine whether or not acoustic variability in and of itself is beneficial in early word learning tasks like the switch task, we tested 14-month-old infants in a version of the switch task using acoustically variable auditory stimuli produced by a single speaker. Results show that 14-month-olds are able to learn phonemically similar words within the switch task with increased acoustic variability and without the presence of multiple talkers.